Child Weight Status: The Role of Feeding Styles and Highly Motivated Eating in Children - Maria A. Papaioannou; Thomas G. Power; Teresia M. O'Connor; Jennifer O. Fisher; Nilda E. Micheli; Sheryl O. Hughes (MDPI AG, 2023)
Although parental feeding plays an important role in child eating and weight status, high food motivation among children may also be a factor shaping how feeding impacts child weight. This study explored whether individual differences in preschool children's food motivation interacted with mothers' feeding styles in predicting subsequent child weight status. Participants included 129 Hispanic Head Start mother/child dyads. Data were collected at ages 4-5 years (Time 1) and 7-9 (Time 3). Staff measured heights/weights and observed children in an eating in the absence of hunger task. Mothers reported on feeding styles/practices and children's eating behaviors. A principal components analysis derived a measure of highly motivated eating in children. Multiple regressions predicted Time 3 child BMI z-scores. Time 3 BMI z-scores were positively predicted by authoritative and indulgent feeding styles and negatively predicted by monitoring. Since feeding style interacted with highly motivated eating, separate regressions were run for high and low food motivation in children. Unexpectedly, results showed that authoritative feeding positively predicted Time 3 child BMI z-scores only for children showing low levels of food motivation. Characterizing differential parental feeding and child eating phenotypes may assist in tailoring childhood obesity prevention programs for the target populations.